Economic Development through Digital Platforms: Exploring Opportunities for Emerging Markets - Zeny Widianingsih; Tedi Herdianto; Wahyu Eko Saputro (Journal of Digital Business and Data Science, 2025)
Digital transformation has changed the structure of the global economy, with digital platforms becoming strategic instruments in accelerating economic development, especially in developing countries. Platforms such as e-commerce, fintech, agri-tech, and edutech provide significant opportunities for micro, small, and medium enterprises (MSMEs) to expand market access, improve operational efficiency, and access financial services. However, the adoption of digital platforms is not free from challenges, including infrastructure inequality, low digital literacy, and weak supporting policies. This study aims to explore the role of digital platforms in the economic development of developing countries and identify the potential, challenges, and strategies to optimize their utilization. The research method used is qualitative with an exploratory case study design in three countries: Indonesia, Kenya, and Colombia. Data were collected through in-depth interviews, participatory observation, and documentation studies. The results show that the use of digital platforms contributes positively to the performance of MSMEs, especially in terms of market expansion and financial inclusion. However, these benefits have not been fully shared due to structural and social barriers. This study emphasizes the importance of local digital ecosystem readiness, adaptive regulations, and cross-sector collaboration in supporting the sustainability of digital transformation. The conclusion of this study is that economic development through digital platforms requires a contextualized and collaborative approach. Practical implications of the findings include the need to strengthen digital literacy, participatory policy support, and the provision of infrastructure and sustainable training for MSME players in developing countries.